Emerging biomarkers in amyotrophic lateral sclerosis: from pathogenesis to clinical applications - Anjum, Farah; Bakhuraysah, Maha; Alsharif, Abdulaziz; Mohammad, Taj; Shamsi, Anas; Hassan, Md. Imtaiyaz (Frontiers in Molecular Biosciences, 2025)
Amyotrophic lateral sclerosis (ALS) is a severe neurodegenerative condition marked by the gradual loss of motor neurons in the brain and spinal cord. As the most common adult-onset motor neuron disease, ALS manifests through gradually worsening muscle weakness that ultimately progresses to complete paralysis. The disease presents in both sporadic and familial forms. Diagnosis is often delayed until substantial and irreversible motor neuron damage has already occurred. Clinical outcomes in ALS have only been defined through large-scale clinical trials with lengthy follow-up periods due to the disease’s inherent heterogeneity and the absence of disease-specific biomarkers. Current biomarker detection methods, such as invasive cerebrospinal fluid (CSF) analysis or advanced imaging, are impractical for routine use, particularly in late-stage ALS. Several blood-based biomarkers have shown promise, including neurofilament levels, cryptic RNA-derived peptides, and immune-mediated changes, which may enable non-invasive monitoring. Nevertheless, the development of these methods is hindered by technical challenges, such as blood matrix interference and low analyte abundance. Among the emerging biomarkers, neurofilament light chain (NfL) appears to be the most promising, as its concentrations change in line with disease progression and distinguish clinically relevant groups. NfL facilitates patient stratification based on clinical progression rates (e.g., rapid vs slow progressors), while cryptic exon-derived peptides, such as UNC13A-derived peptides, enable genetic stratification by identifying molecular subtypes linked to TDP-43 pathology (e.g., C9orf72 vs sporadic ALS). These biomarkers hold promise to optimize clinical trial design through enriched cohort selection and accelerating therapeutic translation by monitoring target engagement. In this review, we have summarized recent developments in ALS biomarker studies, focusing on neurofilaments in each biofluid, transcriptomic signatures, and neuroinflammatory biomarkers, emphasizing technical challenges surrounding reproducibility in measurement. Finally, we discussed the potential integration of these biomarkers into clinical practice to advance drug development through precision medicine, thereby enabling shorter and more targeted clinical trials.